Pola Kesalahan Berpikir Kritis Matematis pada Masalah Trigonometri Kelas X SMA Ditinjau dari Self-Efficacy - Heni Nurhasanah; Makmuri Makmuri; Flavia Aurelia Hidajat; Tian Abdul Aziz (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2026)
Mathematical critical thinking skills are considered one of the essential competencies in 21st-century learning. However, these skills have not developed optimally, particularly in trigonometry, which requires interpretation, visual representation, and mathematical reasoning abilities. In addition to cognitive aspects, mathematical critical thinking skills are also associated with affective factors, one of which is self-efficacy. This study aimed to describe the patterns of mathematical critical thinking errors of tenth-grade students in trigonometry based on their levels of self-efficacy. This study employed a descriptive qualitative approach. The participants were 25 tenth-grade students of SMAIT Thariq Bin Ziyad Bekasi in the 2025/2026 academic year who were grouped into high, moderate, and low self-efficacy categories. The research instruments included a self-efficacy questionnaire consisting of 26 statements and a mathematical critical thinking test in the form of three essay questions developed based on the indicators of interpretation, analysis, evaluation, and inference. Data analysis was conducted through data reduction, data presentation, and conclusion drawing based on the error patterns found in each indicator of mathematical critical thinking. The results showed that the highest percentage of errors occurred in the inference indicator (86.67%) and interpretation indicator (74.67%). Students with low self-efficacy tended to experience errors in most indicators of mathematical critical thinking, whereas students with high self-efficacy showed fewer and relatively minor errors. The findings indicate differences in the patterns of mathematical critical thinking errors based on students’ levels of self-efficacy in trigonometry